The Relationship Between Protected Areas and the International Union for Conservation of Nature: Monitoring and Evaluation Mechanisms - Mohammed Faisal Baqtyyan, (International Journal of Law Research and Studies, 2026)
This study examines the role of international organizations and implementation mechanisms in biodiversity protection, focusing on the International Union for Conservation of Nature (IUCN) as a leading actor in the development of international environmental standards. The study aims to explain how IUCN has contributed to the development of classification systems for threatened species, protected areas, and ecosystems, and to clarify how these standards support the implementation of international conservation obligations. The study also analyzes monitoring and evaluation mechanisms within the international environmental system—particularly Conferences of the Parties and periodic national reports—and assesses their effectiveness in measuring progress toward global biodiversity goals under the Kunming-Montreal Global Biodiversity Framework. Relying on the descriptive-analytical method through the examination of official reports and technical guidelines, the study concludes that IUCN plays a central normative role in global environmental governance.
Keywords: International Union for Conservation of Nature; biodiversity; environmental governance; protected areas; Red List; Conferences of the Parties; national reports